Level of Serum Electrolytes in Chronic Alcoholic Patients - Raut, Mithileshwer; Ghimire, Sangita; Regmi, Prashant; Raut, Sanjay Kumar; Jha, Bharat (Annals of Clinical Chemistry and Laboratory Medicine, 2015)
BACKGROUND: The aim of this study is to establish serum levels of sodium, potassium, magnesium, calcium and phosphorus in chronic alcoholic patients. METHODS: This cross-sectional study was conducted in Tribhuvan University Teaching Hospital (TUTH). A total of 90 chronic alcoholic patients visiting to psychiatry department of TUTH were included in the study. Age of patients ranges from 20-50 years. Study also included 90 non-alcoholic healthy controls that were age matched. RESULTS: Among the 90 chronic alcoholic patients and 90 normal healthy controls, majority of patients (95.5%) and controls (82%) were male, only few patients were female (4.5%). The mean age of the cases and controls were 35.42 ± 5.6 years, 34.53 ± 3.5 years respectively. In this study, the mean values of Serum Sodium and Potassium were lower in cases (133.58 ± 7.8, sodium and 3.64 ± 0.65, potassium) as compared to controls ( 139.43 ± 3.85, sodium and 4.15 ± 0.43, potassium) with the significant correlation in both groups (p<0.001). Calcium, phosphorus and magnesium level was depleted in cases compared to control groups. CONCLUSIONS: Hyponatremia and hypokalemia are the most common electrolyte abnormalities observed in chronic alcoholic patients.